Effects of Melon Seed or Soybean Meal Supplementation on the Physicochemical and Sensory Properties of Incompletely Peeled Cassava Garri - Ikechukwu, Agbara, Gervase; Chikaodili, Ibekwe Paulina (Journal of Food Technology Research, 2020)
In this present study, completely peeled (CP) and Incompletely peeled (IP)cassava roots were used to produce garri, other portions were supplemented with soybean (S) or Melon seed (MS) meals at 10% level and garri were produced, a total of nine which were subjected to physicochemical and sensory analysis using standard procedures and the results presented as mean±SE. The moisture, crude protein, crude fat, total ash, crude fibre and carbohydrate contents varied significantly (P<0.05) from 9.75-15.16%, 1.40-9.71%, 0.70-3.35%, 1.60-2.36%, 2.13-3.45% and 68.97-81.03% respectively. Significance increase was observed in ash, fibre, protein and fat contents of IP garri especially the seed meal treated. Calcium (45-87mg/100g), Phosphorous, Iron and Zinc contents were generally low but Calcium, Potassium and Phosphorous were greater in the IP garri than in the Cp garri, and the values of all the mineral elements were enhanced in the treated garri. The bacteria counts, fungi counts, coliform and staphylococcus aureus load were far below the approved permissible safe limits for ready-to-eat foods however, the E.coli observed in two garri samples could be attributed to post-toasting cross contamination. CP garri had the highest water absorption capacity (4.51%), the swelling index of CP (5.78%), IP (5.90%), and CP+IP (5.76%) were relatively high, and decreased on supplementation with seed meal. The PH of the various garri were slightly acidic especially the untreated garri. The cyanide contents of the various garri (0.11-0.34mg/100g) were low perhaps due to sweet cassava variety used in this study. The sensory properties of the either eba or soaked garri were well appreciated, however the texture of all eba made from IP were softer and stickier. This study has proved that complete removal of the cassava peel for garri production leads to nutrient depletion in a nutrient deficient staple and the waste accumulation constitutes environmental hazard.